Efficacy of Systemic Treatment in Prostate Cancer Patients With Visceral Metastasis: A Systematic Review, Meta-analysis, and Network Meta-analysis - Yanagisawa, Takafumi; Rajwa, Pawel; Kawada, Tatsushi; Mori, Keiichiro; Fukuokaya, Wataru; Petrov, Patrik; Quhal, Fahad; Laukhtina, Ekaterina; von Deimling, Markus; Bianchi, Alberto; Majdoub, Muhammad; Pradere, Benjamin; et al. (The Journal of urology, 2023)
PURPOSE: There are limited pooled data showing the impact of visceral metastasis on oncologic outcomes in metastatic prostate cancer patients treated with combination systemic therapies. We aimed to analyze and compare the efficacy of combination systemic therapies in metastatic hormone-sensitive prostate cancer and metastatic castration-resistant prostate cancer with or without visceral metastasis. MATERIALS AND METHODS: Three databases were queried in July 2022 for randomized, controlled trials analyzing metastatic prostate cancer patients treated with combination systemic therapy (androgen receptor signaling inhibitor and/or docetaxel plus androgen deprivation therapy) to standard of care. We analyzed the association between presence of visceral metastases and efficacy of systemic therapies in metastatic hormone-sensitive prostate cancer and metastatic castration-resistant prostate cancer patients. The main and secondary outcomes of interest were overall survival and progression-free survival, respectively. Formal meta-analysis using fixed-effect model and network meta-analysis using random-effect model were conducted. We followed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) and AMSTAR (A MeaSurement Tool to Assess systematic Reviews) guidelines. RESULTS: Overall, 12 and 8 randomized, controlled trials were included for systematic review and meta-analyses/network meta-analyses, respectively. In metastatic hormone-sensitive prostate cancer patients, adding androgen receptor signaling inhibitor to standard of care improved overall survival in patients with visceral metastasis (pooled HR: 0.77, 95% CI: 0.64-0.94) as well as in those without (pooled HR: 0.66, 95% CI: 0.60-0.72; no differences in both across- and within-trial approach; P = .13 and P = .06, respectively). On the other hand, the progression-free survival benefit from androgen receptor signaling inhibitor + androgen deprivation therapy was significantly lower in patients with visceral metastasis using across-trial approach (P = .03), while it did not reach statistical significance using within-trial approach (P = .14). Analysis of treatment ranking in metastatic hormone-sensitive prostate cancer showed that darolutamide + docetaxel + androgen deprivation therapy had the highest likelihood of improved overall survival irrespective of visceral metastasis. In post-docetaxel metastatic castration-resistant prostate cancer patients, adding androgen receptor signaling inhibitor to androgen deprivation therapy significantly improved overall survival in both patients with visceral metastasis (pooled HR: 0.79, 95% CI: 0.63-0.98) and those without (pooled HR: 0.63, 95% CI: 0.55-0.72). No randomized, controlled trials reported the differential oncologic outcomes stratified by lung vs liver metastases. CONCLUSIONS: Despite aggressive clinical behavior and worse trajectory of metastatic hormone-sensitive prostate cancer and metastatic castration-resistant prostate cancer with visceral metastasis, the effectiveness of novel systemic therapies is similar in both metastatic hormone-sensitive prostate cancer and metastatic castration-resistant prostate cancer patients with and without visceral metastasis. Further well-designed studies with detailed visceral metastatic sites and number will enrich the clinical decision-making.
Keywords: Prostatic Neoplasms, Castration-Resistant; Androgen Antagonists; Receptors, Androgen; Humans; Prostatic Neoplasms; lidé; docetaxel; antagonisté androgenů; androgeny; Docetaxel; nádory prostaty rezistentní na kastraci; Neoplasm Metastasis; Male; protokoly protinádorové kombinované chemoterapie; Network Meta-Analysis as Topic; nádory prostaty; Androgens; mužské pohlaví; antagonisté androgenních receptorů; metastázy nádorů; Androgen Receptor Antagonists; síťová metaanalýza; Antineoplastic Combined Chemotherapy Protocols; androgenní receptory